Student teachers’ perceptions, experiences, and challenges regarding learner-centred teaching - Elize (EC) du Plessis (South African Journal of Education, 2020)
Learner-centred teaching education generally involves methods of teaching that move the focus of instruction from the teacher to the learner. The “learner-centred” label is subsequently attached to teaching strategies, learning events, classroom layout and learning programmes. Aspects such as active learning, learner commitment and the construction of own knowledge are among the principles of learner-centred teaching. Worldwide, the thorough training of teachers is crucial. Every organisation preparing teachers should establish whether they offer suitable qualifications that empower student teachers to cope with the abundant difficulties of the teaching occupation, including learner-centred teaching. The aim of this article is to explore student teachers’ perceptions, experiences, and challenges of learner-centred teaching. To this end, an inquisitive research strategy and qualitative research approach were selected as suitable methodology. Data was collected through a voluntary written assignment set out in student teachers’ teaching practice notebooks. The participants were fourth-year students enrolled at a higher education institution for the Bachelor of Education (BEd) qualification (with speciality in the Foundation Phase). These students were placed in productive, successful schools for the duration of their teaching practicum by the teachers training institution. In addition to their placements, they had to complete their teaching practice at schools in widely differing social environments. The schools’ locations ranged from well-off areas, with good teaching means, to schools in poor areas that were lacking learning support materials. The participants were from diverse cultural groups. Furthermore, the constructivist learning theory was used as theoretical framework. The findings reveal that student teachers have a limited understanding of learner-centred teaching and are currently experiencing three serious challenges with regard to learner-centred teaching. To combat this, guiding principles involving lecturers’ support and involvement, reflection, and the accountable intervention of mentor teachers are suggested.